Relationship of the utilization of ubiquitous technology and technology competency among undergraduates in Malaysian technical universities - Sedek, Muliati; Mahmud, Rosnaini; Ab. Jalil, Habibah; Mohd Daud, Shaffee (Malaysian Technical Universities Network, 2013)
The aim of this paper is to present part of a study done related to the utilization of Ubiquitous Technology among undergraduates in Malaysian Technical Universities. The objectives of the study were to identify (i) the ubiquitous technology utilization level (ii) the undergraduates’ technology competency level and (iii) whether there was a significant relationship between the utilization of ubiqutous technology and technology competency. A total of 101 undergraduates were randomly selected. The study employed the survey method in which the data were gathered through a 5 point-Likert scale questionnaire. Data were analyzed descriptively (mean, frequency and standard deviation), and inferentially (Pearson correlation). The findings of this study revealed that majority of the undergraduates were at high level of ubiquitous technology utilization also found, the undergraduates had high level of technology competency. In addition, results demonstrated that there was a significant relationship between utilization and technology competency.